Effective Social Factors on Farmers' Participation in Establishment of Watershed Management Cooperatives of Fars Province - Gh.H Zamani; B Abadi (تعاون و کشاورزی, 2010)
In new millennium, sustainability of natural resources is a goal which is pursued by development experts and policy makers. Establishing watershed management co-operatives is one of the strategies to attract and convene farmers to participate in decision-making process and present ideas to stop natural resources degradation and to trap damaging waters. The main purpose of this study was to assess farmers' perspective toward factors affecting participation in establishing watershed management co-operatives.  Descriptive research design was conducted using survey method. The population consisted of affiliated farmers in Navayegan Darab co-operative. A random sampling was done to select 30 farmers. A structured questionnaire was used to collect data. A panel of specialists confirmed face validity and a pilot study was done to assess the reliability. The findings indicated that the efforts made by co-operative board members and the amount of their orientation training programs are two main factors that affect their participation in establishing watershed management co-operative. In addition, benefits considered according farmers' perspective were being provided with agricultural inputs and financial credits. The participation constraints for setting up watershed management co-operatives that were expressed by co-operative members were workload and shortage of time; and lack of commitment on the duties and functions of board members